The benefits of forced experimentation: striking evidence from the London Underground network - Larcom, Shaun; Rauch, Ferdinand; Willems, Tim (The quarterly journal of economics, 2017)
We present evidence that a significant fraction of commuters on the London Underground do not travel on their optimal route. We show that a strike on the Underground, which forced many commuters to experiment with new routes, brought lasting changes in behavior. This effect is stronger for commuters who live in areas where the Underground map is more distorted, which points to the importance of informational imperfections. Information resulting from the strike improved network efficiency. Search costs alone are unlikely to explain the suboptimal behavior.
Gesehen am 20.03.2023